Mitigation The Impact of Pandemic through Micro Finance as Catalyst Enhancement Quality of Rural Community Human Resources - Junaidi Junaidi; Sudewi Sudewi; Fauzi Fauzi; Citrawati Jatiningrum (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Pandemic condition affected village community and it turn out become difficulty in fulfill needs and also continue their activity. Quality of Human Resources and community human capital rural considered important one of the strategies carried out in lower poverty is with the microcredit program or the Grameen Bank program to Public country side. The purpose of this study for examine empirical relationship between several influencing factors to the level income with quality of human resources and gender equality effect. Study this is also examine the effect of micro credit to income economy Public countryside. Respondents in this study the customer of microcredit. Analysis method using relevant data quantitative with multiple linear regression. The findings show that the microcredit through the Grameen Bank program improves well-being village community welfare significantly. Keywords : Quality of Human Resources , Microcredit , Community Welfare